Low-frequency radio study of MACS clusters at 610 and 235 MHz using the GMRT - Paul, Surajit; Salunkhe, Sameer; Datta, Abhirup; Intema, Huib
Studies have shown that mergers of massive galaxy clusters produce shocks and turbulence in the intra-cluster medium, the possible event that creates radio relics, as well as the radio halos. Here we present GMRT dual-band (235 and 610~MHz) radio observations of four such clusters from the MAssive Cluster Survey (MACS) catalogue. We report the discovery of a very faint, diffuse, elongated radio source with a projected size of about 0.5~Mpc in cluster MACSJ0152.5-2852. We also confirm the presence of a radio relic-like source (about 0.4~Mpc, previously reported at 325~MHz) in MACSJ0025.4-1222 cluster. Proposed relics in both these clusters are found apparently inside the virial radius instead of their usual peripheral location, while no radio halos are detected. These high-redshift clusters (z=0.584 and 0.413) are among the earliest merging systems detected with cluster radio emissions. In MACSJ1931-2635 cluster, we found a radio mini-halo and an interesting highly bent pair of radio jets. Further, we present here a maiden study of low frequency (GMRT 235&610~MHz) spectral and morphological signatures of a previously known radio cluster MACSJ0014.3-3022 (Abell~2744). This cluster hosts a relatively flat spectrum (α610235∼−1.15), giant (∼1.6~Mpc each) halo-relic structure and a close-by high-speed (1769±148359~km~s−1) merger-shock (M=2.02±0.170.41) originated from a possible second merger in the cluster.